Invisible Authentication, Visible Privacy Costs: The Impact of Frictionless 3DS 2.0 on Consumer Trust, Purchase Completion, and Privacy Concerns in the United States - Himani FNU, (European Economic Letters (EEL), 2026)
One step beyond old methods, 3-D Secure 2.0 changes how people verify payments online – no more constant pop-ups, just quiet checks running behind the scenes. Though faster checkouts often mean more purchases go through, some users worry about what gets tracked when they do nothing at all. Behind this ease lies a web connecting smooth logins, whether buyers feel safe, if deals finish successfully, and unease over unseen data collection. To explore these links among U.S. shoppers, researchers gathered answers from 412 individuals who buy things online. Selection followed a structured method meant to reflect broader shopper patterns across the country. A look at the data shows people know about 3DS 2.0 features, how much they trust smooth login steps, whether they finish buying things online, and how worried they are about private info. Even though easier logins help more purchases go through (β = 0.41, p < .001), those same systems make users feel less safe about their data (β = 0.37, p < .001), which pulls in opposite directions. When tested with deeper math tools, trust plays a mid-level role – linking smoother access to more completed buys (indirect effect = 0.18, p < .01), yet worry over privacy slows down that trust build-up (interaction β = −0.22, p < .01). Younger folks, ages 18 to 34, tend to like seamless sign-ins more, still – they’re also sharper on when companies gather personal details. This lines up with what firms handling payments, stores selling goods, and rule-makers need to weigh: making checkouts fast without hiding how data moves.